Determinación de hemoglobina y hematocrito en niños menores de 9 años de edad del sector Buenos Aires Sur del distrito Víctor Larco - Trujillo durante el mes de junio del 2013 - Alvarado Oruna, César Sneider (2014)
The present work was to determine the levels of hemoglobin (Hb) and hematocrit (HCT) in children under 9 years old Buenos Aires South Sector District Víctor Larco - Lima during the month of June 2013. As the sample consisted of 29 children of both sexes being 14 men and 15 women. Method used was cyanmetha emoglobin microhematocrit. Regarding the results were hemoglobin 41.4% (12 children) normal levels and 58.6% (17 children) decreased levels; and hematocrit 41.4% (12 children) normal levels and 58.6% (17 children) decreased levels also BMI values were determined with a total of 13.8% slow weigth, 62% normal, 3.4% overweight and 20.8% obese. Conclusion of this report found children with decreased levels may possibly have pictures of anemia, which was reported to their parents about the results.